Social motivation in people with and without autism spectrum disorders - Dubey, Indu (2016)
It is commonly observed that people with autism spectrum disorder (ASD) make fewer attempts to have social contact. A recent theory suggests that reduced motivation to have social interactions might be the root for social difficulties in ASD (Chevallier, Kohls, Troiani, Brodkin, & Schultz, 2012). There are currently few simple behavioural ways to test these claims. The aim of this research was 1) to develop a measure of social seeking component of social motivation that is simple enough to be used with a large population of people with ASD; and 2) to test if there is evidence of reduced social seeking in people with ASD. As the first part of this research, I developed and tested a simple behavioural paradigm “Choose-A-Movie” (CAM) that evaluates the effort participants make to view social vs non-social stimuli hence estimating the reward value of the stimuli. It was found that typical adults prefer to watch social stimuli more but they trade-off their stimuli preference for effort. In experiment 2 I used the same paradigm with adults with and without ASD and found that unlike typical adults people with ASD prefer non-social stimuli but they too trade-off their stimuli preference for effort. Having established the efficacy of the CAM paradigm in adults with and without ASD, in experiment 3 I explored CAM’s efficacy for younger participants. A comparison between adolescents with and without ASD on CAM showed that both groups prefer choice requiring less effort, and participants with ASD prefer non-social stimuli to social. However unlike typical adults, typical adolescents did not show a preference for social stimuli. Though these experiments supported the reduced social motivation theory of ASD, they raised questions about the development of social seeking in typical people. Therefore, in experiment 4 I tested participants between ages 4-20 years on CAM. The results showed that typical individuals undergo a decline in their social seeking tendencies during pre-adolescence. This highlights the need for developmental evaluation of social seeking in both ASD and non-ASD populations. Finally, in experiment 5 the CAM paradigm was compared with an Approach-avoidance (AA) task, a frequently used measure of social seeking (Aharon et al., 2001). The findings suggested that social preference could be elicited more strongly in typical adults using CAM paradigm. Furthermore the autistic traits of participants were a reliable predictor of social seeking on CAM but not on AA task. These results raise the question of whether different tools claiming to measure social seeking target the same behaviour. Overall, this research shows that social motivation can be quantified using a simple behavioural paradigm – CAM that targets social seeking component of it, and also that social motivation is reduced in people with ASD. At the same time this research raises important questions about 1) developmental changes in social seeking in typical people, and 2) if different tools of social seeking, measure the same underlying construct. It is important to explore these questions to have a better understanding of social seeking in people with ASD.